Camilo Alonso Vega y sus hombres. Los perpetradores de la Guardia Civil en el primer Franquismo - Arnau Fernández Pasalodos (Rúbrica Contemporánea)
This paper analyses the figure of one of the main perpetrators of the Franco regime: Camilo Alonso Vega. Francisco Franco chose him to lead, organise and supervise the anti-partisan war against the armed anti-Francoist resistance between 1943 and 1952, and under his direction in the Civil Guard, their officers and troops stood out and became executioners. For this reason, this research will analyse the figure and action of these men from the field of study of Perpetrator studies and will make use of the reference bibliography and numerous archival documents for this purpose.